Keshan Disease: A Potentially Fatal Endemic Cardiomyopathy in Remote Mountains of China - Shi, Ying; Yang, Wei; Tang, Xianwen; Yan, Quanhao; Cai, Xiaojing; Wu, Fenfang (Frontiers in Pediatrics, 2021)
Keshan disease (KD) as an endemic, highly lethal cardiomyopathy, which firstly reported in northeast China’s Keshan county in 1935. The mainly clinical manifestations of KD patients include congestive heart failure, acute heart failure and cardiac arrhythmia. Even though some possible etiology, such as viral infection, fungal infection, microelement deficiency, and malnutrition, have been reported, the exact causes of KD remains poorly know. The endemic areas of KD are all remote rural, and many of them are poor and mountainous, places where people are the most socioeconomically disadvantaged in terms of housing, income, education, transportation, and utilization of health services. To date, KD is a huge burden to and severely restricts the economic development of the local residents and health systems of the endemic areas. Although efforts have been made by government area to control, treat, and interrupt disease transmission, the cure or complete eradication of KD are still require global attention. For this reason, in this review, we systemically describe the etiological hypothesis, clinical manifestations, incidence characteristics, and treatment of KD, to enable the better understanding and draw more attention on this non-representative cardiovascular disease, with the aim of accelerating the elimination of KD.